Ground Base Value of Anarchism and Social Security in Indonesia - Sri Pandanari, Dika (Humaniora: Journal of Indonesia Culture and Society, 2023)
The research aimed to find anarchic aspects outside of the misconceptions circulating through the dialectic of anarchism theory and social theory. Anarchism had always been misconceived as an activity that correlated with chaos and brutality or anti-government activity. However, in reality, anarchism had various meanings in several paradigms, such as a system of criticism, a system of thought, moral values, aesthetic values, a way of life, political attitudes, and ideology for some people. The research was conducted through a literature approach and observations on the development of anarchism in Indonesia. In addition, the research aimed to see the potential of the anarchism movement that can influence the social paradigm and influence the development of alternative social movements in Indonesia. It applied a qualitative research methods and literature study as primary data. The results of the research indicate a perspective that the view of anarchism does not always contradict the concept of the state because, in the concept of anarchism, there is an idea of criticism and resistance to an oppressive social system. The social system becomes the real antithesis that can dialectic with the concept of anarchism to produce various criticisms and alternative movements that are effective for social struggles in society. In addition, the potential of anarchism on a small scale is to trigger a self-help movement to develop public awareness towards a better condition because the basic values contained in anarchism are respect for human nature as good, where freedom and morality are the basis of humanity.